The Relationship Between Learning Environment with Learning Outcome Among Santri at the Al-Quran Learning Center Mujahiddin Mosque Bungo Tanjung Anak Air in Padang City - Lily Maulya Dwiyan; Solfema Solfema (Universitas Negeri Padang, 2022)
This research was motivated by the low learning outcomes of students studying at TPA Mujahiddin Bungo Tanjung Anak Air Mosque, Padang City. The low learning outcomes are thought to be due to one of the reasons the learning environment for students is not conducive. This research can be seen the relationship between the learning environment and the learning outcomes of students at TPA Mujahiddin Bungo Tanjung Anak Air Mosque, Padang City. This type of research is a quantitative research with correlational descriptive techniques. The study population was students at TPA Mujahiddin Mosque from grades one, two and three. The sampling technique uses Stratified Random Sampling. The data collection technique is in the form of a questionnaire with a conducive data collection tool; significant learning outcomes between the learning environment and the learning outcomes of Santri at TPA Mujahiddin Bungo Tanjung Anak Air Mosque, Padang City. It is suggested that managers/educators at TPA Mujahiddin Mosque and their parents can support students' learning activities by creating a conducive learning environment so that students can study well.Keywords: learning environment, learning outcomes, TPA